Comparison of international arbitration rules - Kerr, John J., 1950-; Smit, Hans.; Simpson Thacher & Bartlett. International Arbitration Group (Huntington, N.Y. : JurisNet, LLC, 2008)
Compares the arbitral rules of: International Chamber of Commerce (ICC), American Arbitration Association/International Chamber of Commerce (AAA/ICDR), London Court of International Arbitration (LCIA), Stockholm Chamber of Commerce (SCC), and International Center for Settlement of Investment Disputes (ICSID)
Arbitration clause -- Commencement of arbitration -- Constitution of the arbitral tribunal -- General conditions -- Preliminary issues -- Arbitral proceedings -- Arbitral decisions/awards
Includes index
Keywords: Arbitration and award, International